Akt Phosphorylates and Negatively Regulates Apoptosis Signal-Regulating Kinase 1 - Kim, Albert H. (American Society for Microbiology, 2001)
The Akt family of serine/threonine-directed kinases promotes cellular survival in part by phosphorylating and inhibiting death-inducing proteins. Here we describe a novel functional interaction between Akt and apoptosis signal-regulating kinase 1 (ASK1), a mitogen-activated protein kinase kinase kinase. Akt decreased ASK1 kinase activity stimulated by both oxidative stress and overexpression in 293 cells by phosphorylating a consensus Akt site at serine 83 of ASK1. Activation of the phosphoinositide 3-kinase (PI3-K)/Akt pathway also inhibited the serum deprivation-induced activity of endogenous ASK1 in L929 cells. An association between Akt and ASK1 was detected in cells by coimmunoprecipitation. Phosphorylation by Akt inhibited ASK1-mediated c-Jun N-terminal kinase and activating transcription factor 2 activities in intact cells. Finally, activation of the PI3-K/Akt pathway reduced apoptosis induced by ASK1 in a manner dependent on phosphorylation of serine 83 of ASK1. These results provide the first direct link between Akt and the family of stress-activated kinases.